THE STUDY OF LESSON PLANS AND LEARNING ACTIVITIES ON CURRICULUM 2013 BY SEVENTH GRADE ENGLISH TEACHERS AT SMP NEGERI 2 SINGARAJA - ., Kadek Angga Andriani; ., Prof. Dr. Anak Agung Istri Ngr. Marha; ., A.A. Gede Yudha Paramartha, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Studi deskriptif ini bertujuan untuk : (1) menganalisis kualitas RPP kurikulum 2013 yang dibuat oleh guru kelas 7 di SMP N 2 Singraja, (2) menginvetigasi penerapan RPP kurikulum 2013, (3) menginvestigasi permasahalan yang dialami oleh guru dalam menerapkan RPP kurikulum 2013. Subyek penelitian ini adalah dua guru Bahasa Inggris di SMP N 2 Singaraja. Pengumpulan data menggunakan APKCG (penilaian pembelajaran) dan dianalisis menggunakan deskriptif statistic. Hasil dari penelitian ini menunjukan bahwa: (1) Kualitas RPP kurikulum 2013 yang dibuat oleh guru dikategorikan baik (dengan rerata nilai 84). (2) Implementasi RPP dalam kegiatan pembelajaran dikategorikan baik (dengan rerata skor 78). (3) Guru mengalami kesulitan dalam : (a) merancang penilaian, (b) menyusun materi, (c) mengajak siswa melakukan aktifitas menanya dan mengkomunikasikan, (d) menyiapakan media yang cocok. Dapat disimpulkan bahwa implementasi RPP kurikulum 2013 sudah berhasil. Namun, ada yang perlu ditingkatkan dalam beberapa aspek.Kata Kunci : Implementasi kurikulum 2013, Rencana Pleaksanaan Pembelajaran This descriptive study aims at (1) analyzing the quality of lesson plans on curriculum 2013 made by seventh grade English teachers at SMP N 2 Singaraja, (2) observing the implementation of the lesson plans on curriculum 2013, (3) investigating the problems encountered by teachers in implementing lesson plans on curriculum 2013. The subject of this study was two English Teachers of SMP N 2 Singaraja. The data were collected by using APKCG (assessment for teaching) and analyzed by using descriptive statistics. The result of the research shows that: (1) the quality of the lesson plans on curriculum 2013 made by English teachers is good (with the average score of 84). (2)The implementation of lesson plans in learning activities by English teachers is categorized as good (with the average score of 78). (3) Teachers faced difficulty in: (a) designing assessment, (b) organizing material (c) inviting students to do questioning and communicating stage, and (d) preparing appropriate media. It is concluded that the implementation of lesson plans on curriculum 2013 by seventh Grade English Teachers at SMP N 2 Singaraja has been successful. Despite of that, some aspect in implementing lesson plans need to be improved.keyword : Implementation of Curriculum 2013, Lesson plan